2017
DOI: 10.1177/0269215517692641
|View full text |Cite
|
Sign up to set email alerts
|

Electronic visual analogue scales for pain, fatigue, anxiety and quality of life in people with multiple sclerosis using smartphone and tablet: a reliability and feasibility study

Abstract: Electronic visual analogue scales are reliable and useful for people with MS to register fatigue, pain, anxiety and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
0
32
0
1
Order By: Relevance
“…This study provides further evidence for the use of digital technology, including smartphones, for data collection. Other studies in MS have used smartphone apps to (1) assess steps when walking on a treadmill [9]; (2) assess pain, fatigue, anxiety, and quality of life [13]; and (3) assess the feasibility of gathering passive and active performance data [7]. Together with the current analyses, these studies document the focus toward developing digital measures to continuously monitor and assess the MS disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study provides further evidence for the use of digital technology, including smartphones, for data collection. Other studies in MS have used smartphone apps to (1) assess steps when walking on a treadmill [9]; (2) assess pain, fatigue, anxiety, and quality of life [13]; and (3) assess the feasibility of gathering passive and active performance data [7]. Together with the current analyses, these studies document the focus toward developing digital measures to continuously monitor and assess the MS disease.…”
Section: Discussionmentioning
confidence: 97%
“…A recent large-scale study demonstrated that more than 95% of people with multiple sclerosis have access to a mobile device and most use it routinely [10]. Recently published studies have described the use of technologies in developing tools to assess people with multiple sclerosis [7,9,11-13]. In a recent study, it was reported that both healthy participants and people with multiple sclerosis were capable of completing daily tasks on a smartphone for 1 year [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their work concluded that mobile-based assessment approaches were as effective as desktop computer-based approaches. Indeed, mobile phonebased versions of traditional assessment tools have more generally been shown to be as reliable in assessment as their paper-based counterparts, while at the same time making daily assessment easier to facilitate by merit of being available on a mobile phone [43], [44]. This supports the reliability of using cognitive tests within a smartphone-based cognitive fatigue assessment approach.…”
Section: ) Adaptation Of Traditional Cognitive Fatigue Assessment Mementioning
confidence: 85%
“…VAS was originally used as a pain scale; however, it is also useful for other subjective estimates. VAS is now utilized as a tool to assess fatigue in many areas of clinical research 4,5,[11][12][13] .…”
Section: Discussionmentioning
confidence: 99%